Theoretical and methodological directions of research of the history of the Belarusian press in the Soviet period: second half of the 20th century - Zubchenok, Natalya А. (Journal of the Belarusian State University. Journalism, 2023)
The article deals with the main theoretical and methodological directions of studying the history of the Belarusian press in the journalism science of the Soviet period. A review of the main works of domestic scientists was carried out on the analysis of the conditions for the formation and functioning of publications, their socio-political orientation, their role in solving socio-political and cultural problems, the publicistic content of materials. Substantiates the need for scientific understanding of the activities of Belarusian printed publications in different periods of history in order to preserve universal values and state priorities in the modern era of globalisation.
Keywords: history; press; methodology; science; journalism; publicism; politics; culture; literature; society